Developing marketing strategy for family tourist attraction (case study: the heritage palace) - Widyaviriya, Avian Marques; Aprilianty, Fitri (Journal of Business and Management, 2020)
Abstract: Opened on 9 June 2018, The Heritage Palace is the first tourist attraction to offer 3D trick art museum, transport museum, vintage furniture museum, reverse house and classic art-deco-style outdoor garden in the same building. In the development, The Heritage Palace faced many marketing obstacles that were ineffective and unsuitable. This research aims to establish a successful marketing strategy for The Heritage Palace. Internal data from Porter's Value Chain Analysis whereas external data from PESTLE analysis and Porter Five Forces. SWOT analysis conducted to summarize external and internal factors affecting company efficiency, particularly in marketing effort. Additionally, data collection was conducted through interviews with Heritage Palace 's marketing head and social media evaluations (Instagram analysis using Socialbakers and Facebook Audience Analysis). Researchers use the problem tree method to formulate root cause problems based on SWOT data from the organization. Marketing strategies proposed for The Heritage Palace are increasing awareness ofrented facilitation, create a tactical pricing strategy for group visitors, make a discount on ticket prices on the opening day, make a social media campaign about COVID-19 and hire a social media content creator to increase the attractiveness of @theheritagepalace Instagram content.Keywords: COVID-19, Marketing Strategy, The Heritage Palace